Učinkovitost metode recipročnega poučevanja v 5. razredu osnovne šole - Ropič, Marija; Ravnjak, Anja; Kordigel Aberšek, Metka (Revija za elementarno izobraževanje, 2008)
Effective Methods of Reciprocal Teaching in the Fifth Grade of Elementary School. Society offers new information daily, and it is up to us to find the heart of the matter, what is important to us and what we do not need. It is required that readers be skilled in reading different texts and that they know how to use new information in practice. Therefore, readers need a successful reading strategy or a strategy which will help them the most while reading. The purpose of this article was to find the efficiency of the method of reciprocal teaching, which was evaluated in the fifth class of primary school.
Keywords: education; reading; reading comprehension; reading strategies; primary school